Screening of Onion (Allium cepa L.) Genotypes for Acid Tolerance Based on Morpho-physiological and Yield Associated Traits - Sarker, Sajib; Islam, A.F.M. Saiful; Maleque, Md. Abdul; Tabassum, Rehenuma; Monshi, Fakhrul Islam (Journal of Tropical Crop Science, 2022)
Onion is one of the most valuable vegetable crops grown all over the world, but its production is severely affected by abiotic stresses like drought, waterlogging, and the acidic nature of the soil. An experiment was conducted to study the morphological and yield contributing characters of four onion genotypes (Indian Onion-1, Indian Onion-2, Indian Onion-3, and Local onion) in the acidic soil condition at Sylhet region, Bangladesh. The experiment was laid out in a randomized complete block design with three replications. Results showed that four genotypes of onion differed significantly for all the morphological and yield characters. The total yield was positively correlated with plant height, bulb fresh weight, bulb diameter, bulb length, leaf sheath fresh weight, leaf sheath dry weight, root fresh and dry weight. Considering yield and yield attributing traits, Indian Onion-2 performed better in acidic soil and had the highest in bulb fresh weight (72.60 g), total yield (1.78 t.ha-1), and moisture content, followed by Indian Onion-3. Therefore, Indian Onion-2 can be selected as the best genotype for acidic soil in the Sylhet region, Bangladesh.